Low temperature fracture resistance of cement emulsified asphalt mortar under mixed mode I/III loading. (December 2020) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali; Aliha, M.R.M.
Highlights: Fracture resistance (Mode I/III) of cement emulsified asphalt mortar was examined. ENDB specimens at different A/C, W/C ratios and three low temperatures were tested. ANOVA test and regression modeling were conducted at 5% significance level. Fracture toughness is highest in the mode I and lowest value in the mode III. A/C and Temperature have significant impact on KC in all and pure tensile modes. Abstract: Having asphalt in Cement Emulsified Asphalt Mortar (CEAM), this composition has higher toughness and ductility but also higher thermal sensitivity than conventional cement mortar. This study was aimed at investigating the fracture behavior of CEAM under out-of-plane shear and tensile loadings (Mode I, I/III, III) at low temperature. This investigation was performed by testing Edge Notched Disc Bending (ENDB) specimens with different asphalt-to-cement and water-to-cement ratios at three temperatures. Scanning Electron Microscopy technique (SEM was also employed to evaluate the effect of asphalt-to-cement and water-to-cement ratios on the structure of CEAMs. The findings revealed that for CEAM, the fracture toughness attains its highest value at pure tensile mode I, decreases as the share of out-of-plane shear in the mixed-mode I/III loading increases, and reaches its lowest value in the pure out-of-plane shear mode III. Furthermore, a multiple regression model was extracted for the relationship between each critical stress intensity factor (KC ) and asphalt-to-cement ratio (A/C), water-to-cement (W/C), and temperature (T). The analyses showed -at the 95% confidence level- that A/C have a significant impact on KC in all examined modes and also the fracture toughness of CEAM decreases with increasing A/C. Changes in W/C also had a significant impact on the pure shear mode and mixed tensile-shear mode (I/III) stress intensity factors. Temperature changes in the studied range only affected the pure tensile mode stress intensity factor.